Rapid and efficient sequestration of arsenic from contaminated water using hypertolerant Bacillus L-148 sp.: a two-step process - Bagade, Aditi; Nandre, Vinod; Ghosh, Sayanti; Battu, Shateesh; Haram, Santosh; Giri, Ashok; Kodam, Kisan (Green Chemistry, 2019)
A fast, robust and green bioreactor for arsenic sequestration from contaminated water was designed. In the two-tier bioreactor, bacterial arsenite detoxification (1 mM) was carried out followed by precipitation of arsenate in 5 min. The precipitate could be used for supercapacitor applications. This bioreactor yielded arsenic free water, therefore, this method can be adopted for scale-up. The combination of hypertolerant bacteria and fast precipitation indicates the robustness of this pilot bioreactor.

Characterisation of hyper tolerant Bacillus firmus L-148 for arsenic oxidation - Bagade, Aditi; Nandre, Vinod; Paul, Dhiraj; Patil, Yugendra; Sharma, Nisha; Giri, Ashok; Kodam, Kisan (Environmental Pollution, 2020)
Groundwater arsenic pollution causes millions of deaths worldwide. Long term natural and anthropogenic activities have increased arsenic levels in groundwater causing higher threats of arsenic exposure. Arsenic hyper-tolerant Firmicute Bacillus firmus L-148 was isolated from arsenic limiting Lonar lake soil, which tolerated more than 3 M arsenic and could oxidize 75 mM arsenite [As(III)] in 14 days. It oxidized As(III) in presence of heavy metals and had unusual pH optima at 9.2. B. firmus L-148 was studied at the biochemical, protein, genomic and transcript level for understanding its arsenic oxidizing machinery. The proteomic and transcript analysis exhibited the presence of ars and aio operon and supported the inducible nature of ars operon. Robust, hyper-tolerant, fast As(III) oxidizing, least nutrient requiring and multi-metal resistance qualities of the strain were used in microcosm studies for bioremediation. Artificial groundwater mimicking microcosm with 75 mM As(III) was developed. Modulation of carbon source, iron and multi metals affected growth and As(III) oxidation rate. The As(III) oxidation was recorded to be 77% in 15 days in presence of sodium acetate and Fe ions. This microcosm study can be explored for bioremediation of arsenic contaminated water and followed by precipitation using other methods. (C) 2020 Elsevier Ltd. All rights reserved.
Keywords: Arsenic hyper-tolerance; Lonar lake; Microcosm studies; Multi-metal resistance; Next generation sequencing